2016
DOI: 10.1136/bmjopen-2015-010119
|View full text |Cite
|
Sign up to set email alerts
|

Potential workload in applying clinical practice guidelines for patients with chronic conditions and multimorbidity: a systematic analysis

Abstract: ObjectivesTo describe the potential workload for patients with multimorbidity when applying existing clinical practice guidelines.DesignSystematic analysis of clinical practice guidelines for chronic conditions and simulation modelling approach.Data sourcesNational Guideline Clearinghouse index of US clinical practice guidelines.Study selectionWe identified the most recent guidelines for adults with 1 of 6 prevalent chronic conditions in primary care (ie hypertension, diabetes, coronary heart disease (CHD), ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 29 publications
(32 reference statements)
0
60
1
2
Order By: Relevance
“…The number of participants observed, however, accounted for 87.5% (14/16) of all nurses working in the study setting, validly representing nursing activities in the study unit. Although patient disease severity can be a key factor accounting for nursing management (Buffel du Vaure et al, ) and workload (Kraljic et al, ), the conditions of most patients in the study unit were similarly stable; thus it is not possible for us to identify the relationship between patients’ disease severity and nursing work arrangement in this natural setting.…”
Section: Discussionmentioning
confidence: 96%
“…The number of participants observed, however, accounted for 87.5% (14/16) of all nurses working in the study setting, validly representing nursing activities in the study unit. Although patient disease severity can be a key factor accounting for nursing management (Buffel du Vaure et al, ) and workload (Kraljic et al, ), the conditions of most patients in the study unit were similarly stable; thus it is not possible for us to identify the relationship between patients’ disease severity and nursing work arrangement in this natural setting.…”
Section: Discussionmentioning
confidence: 96%
“…Disease treatment can occupy a large part of patients’ day and limit the amount of time they can spend on other activities such as work, studying, leisure, childcare, and being with friends and family. A study found that in order to comply with all disease specific guidelines patients with three chronic conditions (any combination of chronic obstructive pulmonary disease (COPD), coronary heart disease, diabetes, osteoarthritis, hypertension, and depression) would take from six to 13 different drugs a day, visit a health professional 1.2 to 5.9 times a month, and spend a mean (SD) of 49.6 (27.3) to 71.0 (34.5) hours each month in health related activities 2. In patients with all six chronic conditions, the workload rose to 18 medications a day, 6.6 healthcare visits a month, and 80.7 (35.8) hours a month in health related activities 2…”
Section: What Is Burden Of Treatment?mentioning
confidence: 99%
“…6 For patients with multimorbidity, the amount of time required to deal with all health care tasks can be comparable to a part-time job. 7 Thus, in addition to the burden of illness, patients with chronic conditions deal with a "burden of treatment," defined as the health care workload associated with everything they do to care for themselves and its impact on their well-being. 5 Whenever the work imposed on patients for health care competes with demands in their social, family, and professional lives, it may exceed patients' capacity to do it.…”
mentioning
confidence: 99%